Factor affecting islamic fintech adoption by Gen Z in West Java with religion as moderating variable - Br Siregar, Kristina Valentina; Soma, Abdul Mukti; Sitorus, Palti Marulitua (ARKA INSTITUTE, 2024)
In the age of fast digitalization, it’s crucial to comprehend the consumer behavior of the younger generation, particularly in relation to the acceptance of Islamic fintech. This research aims to study the factors that influence Gen Z in adopting Islamic fintech and investigate the potential impact of Religious Orientation. The study uses a questionnaire to collect data from 311 Gen Z in West Java, using SEM-PLS to evaluate the research model and test hypotheses. The results of Smart PLS path analysis revealed that several factors significantly influenced the adoption of Islamic fintech. In particular, perceived risk, financial literacy, perceived benefits and trust, were identified as very important determinants in shaping Gen Z's decision to adopt Islamic fintech. In addition, this study also reveals the important role of religious orientation as a moderator that influences the relationship between perceived risk, perceived benefit, and trust towards the adoption of Islamic fintech by Gen Z in West Java. This study adds to the existing literature on Islamic Fintech adoption and improves understanding of the key drivers in this domain. In addition, this study emphasizes how religious orientation can influence individual attitudes and behaviors regarding the adoption of Islamic Fintech.